2019
DOI: 10.1177/2399654418824602
|View full text |Cite
|
Sign up to set email alerts
|

Decentralization and the quality of public services: Cross-country evidence from educational data

Abstract: In this paper, we study the impact of fiscal and political decentralization on the quality of public service delivery. While the effect of fiscal decentralization on public services is a recursive theme, to the best of our knowledge, our study is the first to investigate the impact of political decentralization. We use educational data as a proxy for the quality of public services. We use microdata from the PISA test scores from 22 countries and test for the impact of fiscal and political decentralization on s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…With different nuances and according to different databases, numerous studies on groups of countries have found evidence favoring the hypothesis that both political and FD improve some facets of educational performance (Busemeyer, 2008; Diaz-Serrano and Meix-Llop, 2012; Falch and Fischer, 2012; Letelier, 2010, 2012; Lindaman and Thurmaier, 2002). However, a study by Hanushek et al.…”
Section: Discussion Of the Literaturementioning
confidence: 99%
“…With different nuances and according to different databases, numerous studies on groups of countries have found evidence favoring the hypothesis that both political and FD improve some facets of educational performance (Busemeyer, 2008; Diaz-Serrano and Meix-Llop, 2012; Falch and Fischer, 2012; Letelier, 2010, 2012; Lindaman and Thurmaier, 2002). However, a study by Hanushek et al.…”
Section: Discussion Of the Literaturementioning
confidence: 99%
“…While this study highlights the limitations of decentralization with regard to income-based achievement gap, it also recognizes its various positive effects. Decentralized systems have been known to depress poverty and reduce various regional inequalities (Diaz-Serrano & Meix-Llop, 2012; Ezcurra & Pascual, 2008; Lessmann, 2009; Qian & Weingast, 1997). Less-developed regions often can offer more attractive investment conditions such as “more flexible labor markets, lower wages, or lower tax rates” that are more attractive than more developed regions and can facilitate “regional convergence” (Diaz-Serrano & Meix-Llop, 2012, p. 7).…”
Section: A Theory Of Strategic Managerial Decentralization and Income-based Achievement Gapmentioning
confidence: 99%
“…Decentralized systems have been known to depress poverty and reduce various regional inequalities (Diaz-Serrano & Meix-Llop, 2012; Ezcurra & Pascual, 2008; Lessmann, 2009; Qian & Weingast, 1997). Less-developed regions often can offer more attractive investment conditions such as “more flexible labor markets, lower wages, or lower tax rates” that are more attractive than more developed regions and can facilitate “regional convergence” (Diaz-Serrano & Meix-Llop, 2012, p. 7). Specifically, managerial decentralization can be beneficial when school districts are dealing with larger student bodies.…”
Section: A Theory Of Strategic Managerial Decentralization and Income-based Achievement Gapmentioning
confidence: 99%
See 2 more Smart Citations